2012
DOI: 10.1111/j.1551-2916.2012.05177.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Foam Properties on Heat Transfer in High Temperature Open‐Cell Foam Inserts

Abstract: Light weight materials such as foams can be used in thermal protection and/or thermal insulation systems. At high temperature (>1000 K), thermal radiation may be important or dominate heat transfer in the foam; however, studies based on more detailed thermal radiation analysis are limited. In this study, foams are considered to be semitransparent, because radiation can penetrate through the pore (or void) space and/or foam skeleton (solid matrix), depending on the materials from which the foams are made. Of pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…The P1 approximation was employed to simulate the radiation transport inside the porous foam, as it is an effective approach that is less time consuming and provides high accuracy [35,36]. For an isotropic scattering medium, the governing equation of the incident radiation, G, was expressed as [37]…”
Section: Governing Equationsmentioning
confidence: 99%
“…The P1 approximation was employed to simulate the radiation transport inside the porous foam, as it is an effective approach that is less time consuming and provides high accuracy [35,36]. For an isotropic scattering medium, the governing equation of the incident radiation, G, was expressed as [37]…”
Section: Governing Equationsmentioning
confidence: 99%
“…A detailed review on the optimal design of foams suggests that micro-architected cellular materials possess superior mechanical properties [5]. Recently, in SiC foams, it was shown that the pore and strut diameter affects the heat transfer (thermal radiation) [6]. The usage of these foams leads to reduction in weight of the structural components, thus increasing the fuel efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Thermal energy storage is an essential method to improve energy efficiency, and it can be used to solve contradictions of heat supply and demand in time and space. [5,6] Phase-change materials (PCMs) for thermal energy storage have received significant attention for their efficient use of thermal energy in recent years. [7][8][9][10] The main advantage of PCMs is that they are able to store heat energy in a latent form, which results in a greater heat storage capacity per unit volume than that of conventional building materials.…”
Section: Introductionmentioning
confidence: 99%